DEVELOPMENT OF TEACHING MATERIALS BASED ON SKILLS OF HYDROCARBON MATERIALS SCIENCE PROCESS FOR VOCATIONAL SCHOOL STUDENTS - Galuh Isna Permata; rusmini rusmini (Universitas Negeri Surabaya, 2023)
Abstract. This study aims to determine the validity, practicality, and effectiveness of teaching materials based on science process skills in hydrocarbon compound material for vocational students. This type of research is development research using 4-D models proposed by Thiagarajan. The targets of this study were 34 students of class XI SMK Negeri 5 Surabaya. The data obtained were analyzed using quantitative analysis methods. The results of the study concluded that science-based teaching skills on the material process of hydrocarbon compounds were declared valid with an average percentage value of 78.00%, expressed very practical with an average percentage interpretation value of 95.15%, and declared effective based on the results of the gain score test which states an increase in science process skills and completeness of student learning outcomes. Keywords: teaching materials, science process skills, hydrocarbon.